Strategic business models field lab: analysis of the peer-to-peer business model in the Ota accommodation industry - recommendation: long-term rentals - Agostinho, José Matias Faro Teixeira Simões (2022)
Despite the harsh impact of the COVID-19 pandemic, the OTA Accommodation industry remains a growing and diverse environment. Utilizing Business Model Analysis as a guiding framework, this Field Lab Report provides insights into the evolution and variation of OTA Accommodation business models. The focus is then narrowed on the Peer-to-Peer Accommodation Model with an analysis of its main components, advantages, and vulnerabilities. Three detailed recommendations are ultimately proposed to strategically optimize this business model and address innovation opportunities. To conclude, key insights and possible extensions are provided. For the individual component of the Field Lab, are commendation to improve the current P2P Accommodation model was elaborated by detailing its business model components and providing implementation considerations from a Business Model Innovation perspective.